2019
DOI: 10.1016/j.chemosphere.2018.11.136
|View full text |Cite
|
Sign up to set email alerts
|

Associations between endocrine disrupting chemicals and equine metabolic syndrome phenotypes

Abstract: Equine Metabolic Syndrome (EMS) is characterized by abnormalities in insulin regulation, increased adiposity and laminitis, and has several similarities to human metabolic syndrome. A large amount of environmental variability in the EMS phenotype is not explained by commonly measured factors (diet, exercise, and season), suggesting that other environmental factors play a role in EMS development. Endocrine disrupting chemicals (EDCs) are associated with metabolic syndrome and other endocrine abnormalities in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In the present study, any acute poisoning sign was not observed at the detected concentrations of POPs in hair samples. Durward-Akhurst et al (2019) investigated the relationship between endocrine-disrupting chemicals (EDC), including PAHs, and equine metabolic syndrome (EMS). Plasma samples were collected from 301 horses, and EDC activity via the aryl hydrocarbon receptor was determined in plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, any acute poisoning sign was not observed at the detected concentrations of POPs in hair samples. Durward-Akhurst et al (2019) investigated the relationship between endocrine-disrupting chemicals (EDC), including PAHs, and equine metabolic syndrome (EMS). Plasma samples were collected from 301 horses, and EDC activity via the aryl hydrocarbon receptor was determined in plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…Detection in doping control laboratories has been based mainly on the testosterone/epitestosterone ratio (T/E) >4 in urine and the presence of other metabolites [28,29]. Nevertheless, in recent years it has been shown that in people who have a genetic deletion of the UGT2B17 gene, which modifies glucuronidation, commonly present a T/E <2, it could allow them to use micro dose steroids and avoid detection [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Fixed and Random EffectsAge and sex were included in our model as fixed effects based on epidemiological studies which identified both as risk factors for EMS [55,56]. Season [57,58], diet [3,59], exercise [59,60], and endocrine-disrupting chemicals [61] have also been identified as environmental risk factors for EMS, but a large percentage of environmental variation has yet to be explained [9]. Further, several studies have produced conflicting findings as to the effect of season on EMS biochemical measurements [62,63], as well as the long-term effect of high non-structural carbohydrate diets on insulin sensitivity [64,65].…”
Section: Appendix A1 Welsh Pony Population Structurementioning
confidence: 99%